Expanding WordNet with Gloss and Polysemy Links for Evocation Strength Recognition - Marek Maziarz; Ewa Rudnicka (Cognitive Studies | Études cognitives, 2020)
Expanding WordNet with Gloss and Polysemy Links for Evocation Strength Recognition